Visual Risk Factors of Asthenopia in Karawo Craftsmen: A Cross-Sectional Study - Fatmawaty Mallapiang; Amalia Jayanti; Lilis Widiastuty; Nildawati Nildawati; Rezki Ramdani (Poltekkes Kemenkes Surakarta, 2026)
Background: Work-related visual strain remains a significant occupational health problem, particularly among workers performing visually demanding tasks. Karawo craftsmen are at increased risk due to prolonged visual focus, suboptimal lighting, and close viewing distances, yet evidence on key contributing factors in this group remains limited. This study aims to analyze the relationship between several visual risk factors, including age, eye-to-object distance, length of service, working hours, lighting, work posture, and medical history, and asthenopia complaints among karawo craftsmen. Methods: The results showed significant associations between age (p = 0.001), eye-to-object distance (p = 0.007), lighting (p = 0.002), and medical history (p = 0.001) and asthenopia among karawo craftsmen. Meanwhile, length of service (p = 0.072), working hours (p = 1.000), and work posture (p = 1.000) were not associated with asthenopia. Results: The results showed significant associations between age (p = 0.001), eye-to-object distance (p = 0.007), lighting (p = 0.002), and medical history (p = 0.001) and asthenopia among karawo craftsmen. Meanwhile, length of service (p = 0.072), working hours (p = 1.000), and work posture (p = 1.000) were not associated with asthenopia. Conclusion: The study found that age, eye-to-object distance, lighting, and medical history were significantly associated with asthenopia complaints among karawo craftsmen. It is recommended that karawo craft entrepreneurs collaborate with local health centers or health services so that elderly craftsmen or those with a history of vision problems can receive regular eye examinations.